1970
DOI: 10.1267/ahc.3.18
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Method of the Prussian Blue Reaction for the Histochemical Demonstration of Iron, and Its Application to the Colloidal Iron Reaction of Acid Mucopolysaccharides

Abstract: In the Prussian Blue method for the histochemical demonstration of iron, some parts of produced pigment are considerably washed away during the dyeing process, because the pigment is water soluble.Consequently decrease and diffusion of the pigment occur and staining of the surrounding tissues take place. The color reaction was carried out in 70% acetone solution in order to decrease the solubility of the pigment.Obtaining the sharp and clear demarcation, this method was applied successfully to the colloidal ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…In Hemerocallis, however, the correlation between the products and nuclear divisions could not be recognized. Hirose et al (1970) have reported that most cellular iron exists as a ferric type and its localization is cytochemically detected with high accuracy by the Prussian blue reaction. On the one hand, cellular iron is recognized in the form of a cytochrome system (Perini et al 1964), polysaccharides (HOf ner 1970), mucopolysaccharide (Hirose et al 1970), and ferritin (Morton 1978).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hemerocallis, however, the correlation between the products and nuclear divisions could not be recognized. Hirose et al (1970) have reported that most cellular iron exists as a ferric type and its localization is cytochemically detected with high accuracy by the Prussian blue reaction. On the one hand, cellular iron is recognized in the form of a cytochrome system (Perini et al 1964), polysaccharides (HOf ner 1970), mucopolysaccharide (Hirose et al 1970), and ferritin (Morton 1978).…”
Section: Resultsmentioning
confidence: 99%
“…Hirose et al (1970) have reported that most cellular iron exists as a ferric type and its localization is cytochemically detected with high accuracy by the Prussian blue reaction. On the one hand, cellular iron is recognized in the form of a cytochrome system (Perini et al 1964), polysaccharides (HOf ner 1970), mucopolysaccharide (Hirose et al 1970), and ferritin (Morton 1978). Judging from the configuration of the reaction products observed in the present study, iron probably exists in the form of ferritin, a crystalline protein present as particles of ferric hydroxidef erric phosphate complex bound to the protein.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the majority of cellular iron exist as a ferric type and that under the light microscope, the blue granular deposits can be visualized as a result of the Prussian blue reaction, which is thought to be the best and most suitable way for the cytochemical localization of cellular iron (Hirose et al 1970;Morton 1978). In the present study, as described above, a 4 % solution of pottasium f errocyanide was used instead of 2 % standard solution of the reagent for an easier recognition of the reaction products.…”
Section: Discussionmentioning
confidence: 99%
“…Hirose et al (1970) have pointed that the Prussian blue deposits are ethanol-soluble, even if the high concentration of ethanol is used. The negative reaction observed in the present study may be attributed to the ethanol treatment for dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was reasoned that the elimination of some steps designed to amplify the modified histochemical stain could improve the resolution of subcellular structures. In addition, a study from 1970 observed that discrete staining of structures could be enhanced by including acetone in the staining solution ( Hirose et al., 1970 ). Acetone was thought to decrease the diffusion of the Prussian blue reaction product leading to greater staining definition ( Hirose et al., 1970 ).…”
mentioning
confidence: 99%